Medication adherence and related psychosocial and clinical factors among schizophrenic patients: a cross - sectional analytical study in National Psychiatric Hospital 2, Vietnam - Tran, Nhu Minh Hang; Nguyen, Van Thinh; Nguyen, Ngoc Quang Linh (Tạp chí Y Dược Huế, 2024)
Background and Aims: Schizophrenia is a chronic and severe mental disorder. Treatment by antipsychotic medication is one of the main therapies to control the symptoms. Medication non/poor adherence is a one of the key factors leading to relapse and declined social and occupational function in patients. However, prevalence of schizophrenic patients with non/poor adherence to medication was quite high in previous studies. Therefore, this study aimed to identify the prevalence of medication non/poor adherence and its related psychosocial and clinical factors among schizophrenic patients. Subjects and Method: a cross - sectional analytical study of 126 schizophrenic patients at National Psychiatric Hospital 2 were conducted to evaluate the rate of medication non-adherence by Morisky Medication Adherence Scale 8 item (MMAS - 8). Data were collected on patients’ sociodemographic factors such as sex, age, marital and economic status, level of education and clinical factors including duration of schizophrenia, clinical symptoms evaluated by Positive and Negative syndrome scale (PANSS), type, and side effects of medication. Logistic regression was used to analyze the factors associated with medication non-adherence among schizophrenic patients. Results: Rate of poor medication adherence among participants was 78.57% by using MMAS – 8. The associated factors with poor medication adherence among schizophrenic patients were level of education under high school; unstable job/unemployment; poor insight about schizophrenia, poor family care/support, high scores of negative PANSS and general PANSS scale, duration of schizophrenia above 5 years, treated by typical antipsychotics and having more than two side effects of antipsychotics. Conclusion: The rate of poor medication adherence/ non - adherence among schizophrenic patients is high. Mental health staff should be aware of this risk and screening individuals for relevant risk factors is highly recommended.